Dental fluorosis and its burden in India-revisiting a forgotten chapter - Rawat, Renu; Aswal, Gunjan S.; Swamy, Dinesh F.; Gurumuthy, Vishwanath; Vishwanath, Soumya (International Journal Of Community Medicine And Public Health, 2020)
“Flouride” mineral is essential for the normal development of bone and teeth. However, its presence in excess of the required limit results in fluorosis of bone (skeletal) and teeth (dental). It is a dominating public health issue in India due to the geographical fluoride belt across numerous states. Dental fluorosis is characterised by the staining and pitting of tooth/teeth. Despite fluoride’s anticariogenic potential, when present in excess amounts, deteriorates aesthetics and cripples the physical, mental and social health of individuals. Numerous government-led initiatives are in place to optimize fluoride levels, unfortunately, with limited coverage and constrained time frame. The overview is an endeavour to assemble the breathing information on dental fluorosis and the obliviousness towards this condition devastating many lives in India. In this manner, stressing on the squeezing need of educational and dental treatment mediations alongside rebuilding of defluoridation programs across the nation.